Health Care Operations and Supply Chain Management : Operations, Planning, and Control - Kros, John F. and Brown, Evelyn C., 1966- (San Francisco Jossey-Bass, a Wiley imprint, 2013)
"This resource provides students with a thorough foundation in operations management, supply chain management, and the strategic implementation of programs, techniques, and tools for reducing costs and improving quality in health care organizations. It incorporates the features and functions of Microsoft Excel where appropriate in its coverage of supply chain strategy, process design and analysis of health care operations, managing health care operations quality, and planning and controlling health care operations. The book illustrates leading edge concepts and techniques such as six-sigma and lean logistics, and shows how operations and process improvement relate to contemporary health care trends such as evidence-based medicine and pay-for-performance"
Include Index
Keywords: Health facilities--Business management -- Health services administration -- Production management